Manajemen dan Kepemimpinan Serta Fungsi-Fungsinya dalam Penjaminan Mutu Pendidikan Islam - Muhammad Arrazi; Titony Tanjung; Zulmuqim (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Management and leadership are crucial for maintaining and improving the quality of education. They are responsible for resource management, curriculum design, the administration of the learning process, and the assessment of the performance of educational institutions within the framework of educational management. Conversely, educational leadership is accountable for inspiring employees, directing goals, and creating a school environment that supports learning. In this article, book research is utilized, signifying research that relies on existing references and literature. The article delves into the meaning of educational management and leadership and how they contribute to enhancing the quality of education. Various interrelated aspects, including the continuously changing context and processes, play a vital role in the issue of educational quality, particularly within the school environment. The importance of understanding and identifying stakeholders' expectations in managing educational institutions demands a well-functioning and accountable management system, as well as the implementation of management functions such as planning, organizing, directing, and controlling.